Cultivars and Production Environments Shape Shoot Endophyte Profiles of Boxwood with Different Blight Resistance - Xiaoping Li; Jerry E. Weiland; Mana Ohkura; Douglas G. Luster; Margery L. Daughtrey; Fred E. Gouker; Gloria Chen; Ping Kong; Chuanxue Hong (PhytoFrontiers)
Phyllosphere colonizers, including bacteria and fungi, are critical for plant growth and health. However, how they are affected simultaneously by the host plant cultivar, local environment, and agricultural practices was not well understood. We used boxwood, an iconic landscape plant and a major evergreen shrub crop in the United States nursery industry, as a model plant and sequenced 16S rRNA and ITS amplicons to examine the assemblages of endophytic bacteria and fungi in the shoots of four cultivars representing three levels of boxwood blight resistance under two distinct climates and production systems in Oregon and Virginia. Cultivar and local environment were the two main drivers shaping the composition and structure of the boxwood endophytic microbial community, particularly the fungal community. Three bacterial and seven fungal genera were consistently identified with high prevalence and abundance as the core taxa from four cultivars and two locations across three sampling times. The microbial composition varied among the levels of boxwood blight resistance, and taxa specific to the tolerant cultivar were fewer compared to the susceptible one. Identification of these microbial indicators, along with the core taxa, is foundational for developing a microbiome-based plant breeding program and a systems approach to improve boxwood health and production under a changing climate. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.